Barriers to the access of oral health care facilities among adults: an exploratory study from Lahore - J. Akram, Shehla; Yasmin, Raheela; Atif, Saira; Rathore, Asadullah; Anjum, Omair; Arshad, Muhammad Bilal; Hameed Khaliq, Imran (Journal of Fatima Jinnah Medical University, 2020)
Background: Oral health is one of the key indicators of the quality of life, overall health and well‑being of the general population. Globally, the high prevalence of the periodontal disease, excessive tooth loss, dental caries experiences, oral cancers and xerostomia are the major issues reported among adult populations. Timely access to oral healthcare facilities preserves the function, morbidity and mortality. The best possible health outcomes are only possible if the personal health care services are accessible timely. So, the primary objective of this study was to explore the barriers to the access of oral health care facilities among adults. In addition, the study also determined the association between adult’s demographic factors and their visits to dental clinics. Subjects and methods: This exploratory study was conducted for two months between November 2019 and January 2020. The study recruited 400 adults including 200 males and 200 females visiting outpatient department (OPD) of public hospital i.e. Jinnah Hospital, Lahore. Participants were included in this study if they were 18 years of age or older and had provided written informed consent before data collection. Data were collected using a structured questionnaire whereas barriers to access the oral healthcare facilities was confirmed by asking an open-ended question. Statistical Package for Social Sciences (SPSS) software was used to calculate descriptive statistics (i.e., mean, standard deviation, percentages). The study also determined the association between sociodemographic factors of adults and their tendency to visit dental clinics just for routine checkups using the chi-square test. Results: The average age of the participants was 36.81±9.29 years ranged from 18 – 63 years. Of the 400 participants, 259 (64.75%) reported costly treatment as a barrier affecting access to oral healthcare facilities followed by difficulty in access to dental clinics (27.75%) and fear of the pain of dental procedures (20.25%). Only 52 (13%) adults were regularly visiting dental clinics for routine check-ups whereas 21 (5.25%) respondents never had been to the dentist throughout their life. Nearly, half of the respondents i.e. 189 (47.25%) stated that dental care expenditures were borne by them and none of them was health insured. Statistically, a significant association was found between demographics (i.e. education, rural background and income) and the tendency to visit the dental clinics (p<0.05). Conclusion: Expensive treatment, difficulty in accessing dental facilities and fear from dental procedures are the major barriers to the utilization of dental services. Access to dental clinics for routine check-ups is significantly influenced by sociodemographic factors.